Multi-state systems with selective propagated failures and imperfect individual and group protections - Levitin, Gregory; Xing, Liudong; Ben-Haim, Hanoch; Dai, Yuanshun (Reliability engineering & system safety, 2011)
The paper presents an algorithm for evaluating performance distribution of complex series–parallel multi-state systems with propagated failures and imperfect protections. The failure propagation can have a selective effect, which means that the failures originated from different system elements can cause failures of different subsets of elements. Individual elements or some disjoint groups of elements can be protected from propagation of failures originated outside the group. The protections can fail with given probabilities. The suggested algorithm is based on the universal generating function approach and a generalized reliability block diagram method. The performance distribution evaluation procedure is repeated for each combination of propagated failures and protection failures. Both an analytical example and a numerical example are provided to illustrate the suggested algorithm. ► Systems with propagated failures and imperfect protections are considered. ► Failures originated from different elements can affect different subsets of elements. ► Protections of individual elements or groups of elements can fail with given probabilities. ► An algorithm for evaluating multi-state system performance distribution is suggested.